Quantum Logic Explorer |
< Previous
Next >
Nearby theorems |
||
Mirrors > Home > QLE Home > Th. List > lem3.3.7i2e3 | GIF version |
Description: Equation 3.7 of [PavMeg1999] p. 9. The variable i in the paper is set to 2, and this is the third part of the equation. (Contributed by Roy F. Longton, 3-Jul-05.) |
Ref | Expression |
---|---|
lem3.3.7i2e3 | (a →_{2 }(a ∩ b)) = (a →_{1 }b) |
Step | Hyp | Ref | Expression |
---|---|---|---|
1 | nom12 309 | 1 (a →_{2 }(a ∩ b)) = (a →_{1 }b) |
Colors of variables: term |
Syntax hints: = wb 1 ∩ wa 7 →_{1 }wi1 12 →_{2 }wi2 13 |
This theorem was proved from axioms: ax-a1 30 ax-a2 31 ax-a5 34 ax-r1 35 ax-r2 36 ax-r4 37 ax-r5 38 |
This theorem depends on definitions: df-a 40 df-i1 44 df-i2 45 |
This theorem is referenced by: (None) |
Copyright terms: Public domain | W3C validator |